Engineering management in a global environment : guidelines and procedures - Atesmen, M. Kemal (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2017)
Annotation